Evaluation Study of Short Stay Homes for Women and Girls (An Interim Report) - Planning Commission (Planning Commission, 1998)
"The paradigms for social development have been changing with greater attention to gender issues at the global and national levels. The development of women in India has been in the centre stage of developmental planning right from independence. Despite this, atrocities on women is on the increase. The crime rate i.e. incidence of crime per one lac of population of women was as high as 11.6 in 1995. Rapid industrialisation, urbanisation and break up of the institution of joint families have led to social problems of adjustment among women and girls."
Programme Evaluation Organisation, Planning Commission Government of India